Austenite formation in a ferrite/martensite cold-rolled microstructure during annealing of advanced high-strength steels. Issue 1 (14th February 2014) - Philippot, C.; Drillet, J.; Maugis, P.; Hebert, V.; Dumont, M.
Abstract : From a ferrite/martensite cold-rolled microstructure, the interaction between ferrite recrystallization and austenite formation is investigated. It is observed that a slow heating rate promotes the ferrite recrystallization and a homogeneous microstructure, whereas a fast heating rate delays the recrystallization and leads to heterogeneously distributed austenite islands.